Are lizards feeling the heat? A tale of ecology and evolution under two temperatures - Meiri, S.; Bauer, A.M; Chirio, L.; Colli, G.R; Das, I.; Doan, T.M; Feldman, A.; Herrera, FC; Novosolov, M.; Pafilis, P.; Pincheira-Donoso, D.; Powney, G.; et al. (John Wiley & Sons Ltd, 2013)
Lizards with low body temperatures do not seem to have ‘slower’life-history attributes than species with high body temperatures.The longer seasons prevalent in warm regions, and physiological processes that operate while lizards are inactive (but warm enough), make environmental temperatures better predictors of lizard life-history variation than body temperatures. This surprisingly greater effect of environmental temperatures on lizard life histories hints that global warming may have a profound influence on lizard ecology and evolution.